Peran Pemeriksaan Keparahan Inkontinensia Fekal dengan Kuisioner FISI pada Kelompok Lanjut Usia - Peter Ian Limas; Alexander Halim Santoso; Heri Yanto Putra; Ryan Dafano Putra Mahendri; Edwin Destra; Farell Christian Gunaidi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Fecal incontinence (IF) is the inability to control the release of feces, often occurring in the elderly due to decreased physiological function of the pelvic muscles. Assessment of the severity of fecal incontinence requires a valid instrument such as the Fecal Incontinence Severity Index (FISI), which is based on a score to classify IF conditions. This community service activity was carried out with 93 elderly participants who took part in the FISI examination and education in order to increase understanding of the severity of fecal incontinence and the importance of preventive measures through early detection. The education program was carried out using the PDCA (Plan-Do-Check-Act) method which provides information related to risks, preventive efforts, and healthy lifestyle-based management steps. The average FISI score shows variations in severity among participants, providing an objective picture of the condition of the elderly. FISI acts as an important evaluation tool for monitoring and education, helping the elderly and their families understand their condition and take preventive measures. FISI examination in this program improves the quality of life of the elderly through effective education and prevention strategies